Do immigrants attract FDI? District-level evidence from Germany - Chen Li (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Using novel German district-level data from 1999-2011, this paper analyses whether the presence of immigrants in a particular location helps to attract inward FDI from the immigrants' country of origin. Results show that a one standard-deviation increase in the immigrant share is associated with a 3.3% rise in firm entry. This effect is stronger for an investor's first entry into Germany, and there is indication that firms from developing countries depend more on immigrants. A quasi-natural experiment exploiting the migration of ethnic Germans from the former Soviet Union in the 1990s (`Sp taussiedler') confirms the results.
Keywords: F14; F22; F23; 330